SANDSTONE RESERVOIR CHARACTERIZATION USING EXTENDED ELASTIC IMPEDANCE INVERSION METHOD OF TAWUN FORMATION, - Rizky Al Harits, Amal
The East Java Basin is one of the regions with hydrocarbon reservoir potential in Indonesia. One of the natural gas-producing fields in the East Java Basin is the "AMASTA" field, which has hydrocarbon reservoirs in the Tawun formation, the focus of this research. The reservoir is composed of interbedded sandstone and shale with limestone intercalations. The research aims to determine the lithology and distribution zones of hydrocarbon reservoirs based on seismic volume inversion.To achieve the research objectives, it is necessary to determine sensitive elastic parameters and use an appropriate inversion method. Sensitivity analysis on log data indicates that the elastic parameters sensitive for determining reservoir zone distribution are AI (Acoustic Impedance) and vp/vs (P-wave to S-wave velocity ratio). The inversion method used in this research is Extended Elastic Impedance, employing an optimal correlated angle with the elastic parameter vp/vs ratio. Reflectivity volumes are created using P-wave reflectivity (Rp) and S-wave reflectivity (Rs) volumes, generated using the AVO two-term Ursenbach-Stewart equation (2008). Subsequently, these volumes are transformed into EEI (Extended Elastic Impedance) reflectivity using the equation by Whitcombe et al. (2002). Inversion is performed on EEI reflectivity using the Linear Programming Sparse-Spike inversion. The inversion results indicate the potential presence of hydrocarbon reservoir zones directly beneath the Lower Tawun-1 (LTA-1) horizon, characterized by hydrocarbon-filled sandstone with vp/vs ratio values below 2.2